2014
DOI: 10.1111/1365-2478.12102
|View full text |Cite
|
Sign up to set email alerts
|

Relating electrical conduction of alluvial sediments to textural properties and pore‐fluid conductivity

Abstract: Electrical conductivity of alluvial sediments depends on litho‐textural properties, fluid saturation and porewater conductivity. Therefore, for hydrostratigraphic applications of direct current resistivity methods in porous sedimentary aquifers, it can be useful to characterize the prevailing mechanisms of electrical conduction (electrolytic or shale conduction) according to the litho‐textural properties and to the porewater characteristics. An experimental device and a measurement protocol were developed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…This clearly indicates that in the southern region of the study area, the hydrological units are protected from being exposed to interaction with the brackish water for borehole depths greater than 40 m due to hydrogeological formation divide. However, the conductivity of water increases (the resistivity decreases) toward the north due to divides between formations and geological formations in the study area (Mauro et al 2014). …”
Section: Resultsmentioning
confidence: 93%
“…This clearly indicates that in the southern region of the study area, the hydrological units are protected from being exposed to interaction with the brackish water for borehole depths greater than 40 m due to hydrogeological formation divide. However, the conductivity of water increases (the resistivity decreases) toward the north due to divides between formations and geological formations in the study area (Mauro et al 2014). …”
Section: Resultsmentioning
confidence: 93%
“…Archie found that the bulk electrical resistivity (q b ) is related to pore-water resistivity (q w ) as shown in Eq. (1) for a fully saturated and clay-free formation (Keller and Frischknecht, 1966;Mauro et al, 2014). The formation factor (F) represents a macroscopic property of rock/soil and can be expressed, in its simplest form in Eq.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…However, Archie's law does not take into account surface conduction, which is more and more significant as the amount of clay minerals increases. Anyway, even when this law is modified to consider surface conduction (Clavier et al, 1984;Mele et al, 2014;Waxman and Smits, 1968), it is only valid for a single conducting phase that partially saturates a non-conducting matrix. Recently, a generalization of Archie's law to n-conducting phases has been proposed by Glover (2010), who also provides a summary of the most common mixing models for electrical conductivity in porous media.…”
Section: Combining Van Genuchten and Archie Modelsmentioning
confidence: 99%